Adaptive Traditional Assistive Technology to Support the Motor Development of Children with Special Needs in Early Childhood Education: An Ethnographic Study of Inclusive Pedagogical Practices - Halimatul Saqdiyah; Jhoni Warmansyah; Rohan Kumar; Nikhil Desai (Journal of Paddisengeng Technology, 2026)
Background. Inclusive early childhood education requires learning environments that accommodate the diverse motor abilities and participation needs of children with special educational needs. Traditional play tools have strong cultural and pedagogical value, yet their potential as low-tech assistive technology remains underexplored, particularly when systematically adapted to children’s individual motor characteristics. Purpose. This study aims to explore how traditional play tools are adapted and integrated as low-tech assistive technology to support motor development, participation, and inclusive pedagogical practices among children with special educational needs. Method. An educational ethnography systematically observed 27 children in one inclusive West Sumatran classroom using observations, interviews, field notes, motor-response records, documentation, and teacher-mediated adaptation analysis. Novelty. This study reframes culturally familiar traditional play materials as adaptive low-tech assistive technology through individualized modifications and iterative teacher-responsive pedagogy. Results. Adapted traditional play tools improved accessibility and supported motor engagement, independence, participation, and peer interaction among children with special educational needs. Teacher responsiveness emerged as a key factor in aligning tool adaptations with individual abilities. Conclusion. Traditional play tools can function as culturally responsive low-tech assistive technology when systematically adapted to children’s motor needs. Their effectiveness is shaped by cultural familiarity, functional adaptation, and continuous teacher support.